Hypothermia Reduces Toll-Like Receptor 3-Activated Microglial Interferon-β and Nitric Oxide Production - Tomohiro Matsui; Yukari Motoki; Yusuke Yoshida (Hindawi Limited, 2013)
Therapeutic hypothermia protects neurons after injury to the central nervous system (CNS). Microglia express toll-like receptors (TLRs) that play significant roles in the pathogenesis of sterile CNS injury. To elucidate the possible mechanisms involved in the neuroprotective effect of therapeutic hypothermia, we examined the effects of hypothermic culture on TLR3-activated microglial release of interferon (IFN)-β and nitric oxide (NO), which are known to be associated with neuronal cell death. When rat or mouse microglia were cultured under conditions of hypothermia (33°C) and normothermia (37°C) with a TLR3 agonist, polyinosinic-polycytidylic acid, the production of IFN-β and NO in TLR3-activated microglia at 48 h was decreased by hypothermia compared with that by normothermia. In addition, exposure to recombinant IFN-β and sodium nitroprusside, an NO donor, caused death of rat neuronal pheochromocytoma PC12 cells in a concentration-dependent manner after 24 h. Taken together, these results suggest that the attenuation of microglial production of IFN-β and NO by therapeutic hypothermia leads to the inhibition of neuronal cell death.